A Statistical Survey on the Socioeconomic and Demographic Livelihood of Brick Kiln Workers: A Case Study of Bahawalpur District, Punjab, Pakistan - Fakhra Anwar; Muhammad Mohsin; Sana Arshad (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
The working population at the brick kilns is considered as the people living under poverty line. This study aims to investigate the socioeconomic and demographic characteristics and housing and living conditions of the brick kiln workers in Bahawalpur district. Total 20 kilns were visited in 5 tehsils of the district as sample sites. A questionnaire was designed and a field survey was conducted by using simple random sampling techniques to collect the data of 400 workers from 20 brick kilns. The quantitative analysis was performed in Statistical Package for Social Sciences (SPSS) v. 21 by applying descriptive and inferential statistics. Findings showed that majority of the workers and heads of working households were male (85.75% and 97.5% in rural and urban kilns respectively) and Saraiki speaking (70%) belonged to Muhajir, Ranagr and Khokhar castes. The early age (14-18 years) marriages were common among the workers especially among the females. Dependency ratio of the kiln workers was 37.6% including mostly the children and aged. Dominant share of the kiln workers (70-80%) were illiterate and very few were literate from primary to intermediate level. The workers’ income varied between PKR 11,000 to 15,000 which was lower than the average wage (PKR 25,000) as per the government rules. Brick moulders and soil suppliers were the main occupants at kilns. Most of the workers were resided in their own houses (1 or 2 rooms) made with kacha (mud made) material. Although various facilities were available to the to the workers at brick kilns but they have limited or no proper access to safe drinking water (20%), first aid and Medicare (18%) and accident risk prevention (0%) crucial for their health. Thus, these facts demonstrated that kiln workers led a meagre life style. This work will serve as a reminder to authorities, planners and Non-Governmental Organizations (NGOs) to take action to improve the living conditions of kiln workers. Lastly, few suggestions were proposed to uplift the lives of the kiln workers.